Two pregnancy cases of uterine scar dehiscence after laparoscopic myomectomy - Song, Soo-Youn (Obstet Gynecol Sci, 2015)
Uterine scar dehiscence following laparoscopic myomectomy rarely occurs but can compromise both maternal and fetal well-being in subsequent pregnancy. We here present two cases of pregnancy complicated by preterm birth that resulted from uterine scar dehiscence following laparoscopic myomectomy. First case was a nulligravida who had scar dehiscence at 26 weeks of gestation after having a laparoscopic myomectomy 3 months prior to conception. Two weeks later, we observed her fetal leg protruding through the defect. The other case was a primigravida with a history of prior cesarean delivery, whose sonography revealed myomectomy scar dehiscence at 31 weeks of gestation. Within a few hours after observing, the patient complained of abdominal pain that was aggravating as fetal leg protruded through the defect. In both cases, babies were born by emergency cesarean section. Conservative management can be one of treatment options for myomectomy scar dehiscence in preterm pregnancy. However, clinicians should always be aware of the possibility of obstetric emergencies.